A High Frequency Converter for EV Application - G. Kannan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
An electrical vehicle (EV) is advancing as alternative power trains for green transportation. the DC–DC converter for auxiliary power supply of electric loads .In this paper presented  a new topologyof  high frequency converter for electric vehicle was proposed,This converter has to be capable of handling the energy transfer from the 28V DC bus and the 550 high voltage DC bus (used for the electric traction). The control strategy is phase shift of the full bridge converter. Using this topology we reduce the switching losses. Conventional converter at two levels of voltage by only one full bridge converter using two planar transformers in high frequency the primary are coupled in parallel and the secondary are in series. We minimized the size and the weight of the converter. The high frequency converter advantages in terms of cost, efficiency, flexibility, and increased due to the possibility of easy synchronous rectification implementation.